Barriers to accessing emergency contraception by victims of sexual assault in Addis Ababa, Ethiopia - Kassa, Munir; G.Hiwot, Yirgu; Abdella, Ahmed (Ethiopian Journal of Reproductive Health, 2018)
Background: Medical support including rape management to victims of sexual assault are not well organized and readily available to those who require this service in Addis Ababa. Objective: This survey aimed at examining the potential barriers to accessing emergency contraception (EC) among sexual assault survivors in Addis Ababa, Ethiopia. Methods: This is a quantitative and qualitative study conducted in July of 2006 in Addis Ababa, Ethiopia. The quantitative component was a survey of all hospitals in the city using a standardized questionnaire to evaluate the provision of EC for sexual assault victims. Since sexual assault victims often report to the police, the study included an in-depth interview with police women who were dealing with such cases. Results: Five public hospitals and one model clinic of the Family Guidance Association of Ethiopia (FGAE) give treatment to victims of sexual assault in Addis Ababa. No private hospital provides treatment for such cases as the police do not refer such cases. Though there are five public hospitals, one of them has got a model rape clinic. In the survey, most victims of sexual assault were seen in the FGAE model clinic. This is because the police perceive that the service given by government hospitals is of poor quality. All public hospitals provide EC, a dedicated product called ‘Postinor 2’ free of charge. The interviewed police women had very little knowledge about EC, though they have worked for a long time with sexual assault victims. According to police women who worked for more than six years, most victims did not come within 3-5 days after the assault. And when victims do come, they often first visit police stations not hospitals. It was also found out that it is the police who determine as to where these victims should get treatment. Conclusion: Public hospitals should improve the quality of service they provide to victims of sexual assault. It is crucial to provide health education on EC to community members and the police working with victims of sexual assault in order to ensure that patients seek care early to prevent unwanted pregnancy and receive timely and appropriate medical certificates to legal bodies. Furthermore, ways should be sought to increase the involvement of private hospitals in the management of victims of sexual assault in Addis Ababa. Keywords: Emergency contraception; legal bodies; sexual assault; gender